x = 2 a − b ± b 2 − 4 a c
Using the quadratic formula above, find the roots of the equation
x 2 − 2 0 x − 6 9 = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The normal equation looked like x 2 − 2 0 x − 6 9 = 0 . But we will change the subtraction to the addition of the opposite to make it look like x 2 + ( − 2 0 x ) + ( − 6 9 ) = 0 .he first number of the equation is inserted into A (in this case 1). The second number inserted for b (-20). And the third number for C (-69). In the end we put all the numbers in the quadratic formula to make: 2 ∗ 1 ( − 2 0 ) ± ( − 2 0 ) 2 − 4 ∗ 1 ∗ ( − 6 9 ) = 2 3 , − 3
Hey bro, You should check your quadratic formula again.
The formula is wrong
I'm very sure that even 4ac comes under the root; not just b 2 and -b not just b.
x 2 − 2 0 x − 6 9 = 0 → ( x + 3 ) ( x − 2 3 ) = 0 ⇒ x = − 3 , 2 3 .
Problem Loading...
Note Loading...
Set Loading...
Using the quadratic formula
x = 2 2 0 ± 2 ( − 2 0 ) 2 − 4 ( 1 ) ( − 6 9 ) = 1 0 ± 2 4 0 0 + 2 7 6 = 1 0 ± 1 3
⟹ x = 1 0 + 1 3 = 2 3
⟹ x = 1 0 − 1 3 = − 3
Substituting the values of x into the equation, we have
when x = 2 3
2 3 2 − 2 0 ( 2 3 ) − 6 9 = 0
5 2 9 − 4 6 0 − 6 9 = 0
6 9 − 6 9 = 0
0 = 0 (The statement is true)
when x = − 3
( − 3 ) 2 − 2 0 ( − 3 ) − 6 9 = 0
9 + 6 0 − 6 9 = 0
6 9 − 6 9 = 0
0 = 0 (The statement is true)
Therefore, the roots are 2 3 and − 3 .